ECOLOGICAL VALIDITY OF A NOVEL SCORING METHOD FOR TRAIL MAKING PART B: APPLICATION TO REAL-WORLD DRIVING SKILL. (11th November 2018) - Sofko, C; Ahern, D; Davis, J; Kenney, L; Correia, S; Ott, B
Abstract: The cognitive skills needed to successfully complete Trail Making Test Part B (TMT-B) may also be important for driving. The standard cut-off time of 300s for TMT-B limits clinical assessment and research analysis and creates a spuriously restricted range. The purpose of this study was to apply the TMT-B Efficiency Score (TMT-Be), which increases variability among those unable to complete the task in 300s, to a sample of older adults who also completed an on-the-road driving evaluation. Data were obtained from N=146 cognitively impaired and cognitively intact individuals in the Providence, Rhode Island area as part of a larger driving study. Of those with complete data (n=114), most (96.5%) were White, the average age was 74.9 years (SD=7.20), and most were female (58.8%). The correlation between TMT-B total time in seconds and global driving rating was significant, and as the time to completion increased (worse performance), worse driving scores were obtained (rs=0.456, p <0.001). Spearman's correlations revealed significant associations between worse TMT-Be performance and worse driving rating scores (rs=0.474, p <0.001). Error types on TMT-B were also analyzed, and a significant correlation emerged such that perseveration errors were associated with worse driving ratings (rs=0.283, p= 0.002). Comparison of TBT-Be to another pro-rated scoring method (Heaton et al., 2004) revealed a significant correlation in the expected direction (rs=0.224, p=0.017). Overall, TMT-Be may be an important research tool that increased the variability among those unable to complete the task in 300s. Additional research and clinical applications of TMT-Be will be discussed.